Toxoplasma gondii Genotyping: A Closer Look Into Europe - Fernández-Escobar, Mercedes; Schares, Gereon; Maksimov, Pavlo; Joeres, Maike; Ortega-Mora, Luis Miguel; Calero-Bernal, Rafael (Frontiers in Cellular and Infection Microbiology, 2022)
Toxoplasma gondii is a major zoonotic agent which may cause harmful effects mainly in pregnant and immunocompromised hosts. Despite many efforts on its genetic characterization, an entirely clear picture of the population structure in Europe has not been achieved yet. The present study aimed to summarize the available genotyping information and to map the distribution of circulating strains. There is consensus on type II T. gondii genotypes prevailing in Europe, but the absence of harmonization in the use of typing methods limits detailed knowledge. Standardized, high-end typing tools and integrative strategies are needed to fill the gaps and complete an accurate image of the T. gondii genetic population in Europe.